Therapeutic review of cabotegravir/rilpivirine long‐acting antiretroviral injectable and implementation considerations at an HIV specialty clinic. Issue 8 (5th July 2021) - Howe, Zach W.; Norman, Sarah; Lueken, Abbie F.; Huesgen, Emily; Farmer, Eric K.; Jarrell, Kaitlyn; Mathis, Joscelyn E.; Bonham, Kyle W.; Hahn, Julie
Abstract: Cabotegravir/rilpivirine (CAB/RPV) was recently approved by the US Food and Drug Administration (FDA) as the first complete parenteral antiretroviral (ART) regimen for treatment of people living with HIV (PLWH). As a monthly intramuscular (IM) injection, this therapy constitutes a major departure from the traditional paradigm of oral therapy requiring (at least) daily administration that has defined HIV treatment for decades. Composed of a second‐generation integrase inhibitor (INSTI) and nonnucleoside reverse transcriptase inhibitor (NNRTI), CAB/RPV has achieved high rates of sustained virologic suppression with a favorable safety profile for treatment‐experienced PLWH following oral lead‐in (OLI) during several clinical trials. In addition to the clinical benefits of this agent, patient‐reported outcomes associated with convenience, confidentiality, and the tolerability of the injections have consistently reflected positive perceptions of CAB/RPV. The novel nature of this therapy in the field of HIV presents logistical challenges. Clinics will need to address barriers related to management of clinic workflow, procurement, reimbursement, and nonadherence. The aim of this review was to summarize the available safety, efficacy, and pharmacokinetic/pharmacodynamic (PK/PD) data of this long‐acting (LA) injectable regimen as well as discuss some potential considerations for prescribing and operationalization.